Mechanism of the historical and the ongoing Vulcanian eruptions of Ebeko volcano, Northern Kuriles - Belousov A.; Belousova M.; Auer A.; Walter T.R.; Kotenko T. (My University, 2021)
Ebeko is one of the most active volcanoes of the Kurile island arc, producing frequent mild Vulcanian explosions with eruption clouds up to 5 km high. The volcano poses a serious threat to the Severo-Kurilsk town with a population of around 2500 inhabitants, located at a distance of only 7 km on a fan of the volcano’s laharic deposits. Here, we report an overview of the activity of the volcano in the 20th–21st centuries and the results of our geological and petrological investigations of the ongoing Vulcanian eruption that started in 2016. We have found that eruptions of Ebeko span a range of mechanisms from purely magmatic to phreatic/hydrothermal. Three of its historical eruptions (the 1934–1935, 1987–1991, and the 2016–ongoing) involved fresh magma, while during the others (1967–1971, 2009–2011) fresh magma was not erupted. Juvenile material of the ongoing eruption represents highly crystalline and highly viscous (more than 108 pa s) low-silica (56–58 wt% SiO2) andesite. Historical data and our observations of the ongoing eruption allowed us to suggest a functional model of the volcano where Vulcanian explosions are caused by shallow intrusions of small diapir-like batches of strongly crystallized and highly viscous andesitic magma ascending into water-saturated, hydrothermally altered rocks composing the volcano summit. We suggest that the diapir’s ascent is governed by their positive buoyancy. Some of the diapirs reach and breach the ground surface producing magmatic eruptions of Ebeko, while the others are stuck at the shallow subsurface level and feed intensive hydrothermal activity as well as phreatic eruptions of the volcano. Positive buoyancy of the diapirs is too weak to allow them to extrude high above the ground surface to form lava domes.
Keywords: Kurile islands; Ebeko volcano; Historicalerupions; Mechanism of Vulcanian explosions; Magma diapir; Lava dome